Development of SERVQUAL Service Quality Measurement Instrumen in Primary School - Ratna F Hapsari; Yarsi Efendi; Dinda Nurul Inayati; Desi K Wulansari; Iyan Irdiyansyah (FKIP UNIVERSITAS PAKUAN, 2025)
This research aims to focus on developing a measurement tool for assessing service quality in primary schools utilising the ADDIE model. The development process consists of five key phases: analysis, design, development, implementation, and evaluation. By applying the ADDIE framework, the study successfully established an instrument to evaluate educational service quality at Public Elementary School in South Tangerang. The process followed a systematic approach through these five stages. In the Analysis phase, the study found that the SERVQUAL model is particularly suitable for assessing educational service quality in primary education. During the Design phase, the questionnaire was validated by experts without requiring any modifications, confirming its content validity. In the Development phase, 23 out of 26 statements were deemed valid, resulting in a reliability score of 0.812, indicating the instrument's consistency. The Implementation phase confirmed the validity and reliability of all statements on a larger scale, achieving a Cronbach's alpha of 0.924. Finally, the Evaluation phase gathered feedback that endorses the instrument's effectiveness while identifying areas for future enhancement. Overall, this research illustrates that the developed tool is both valid and reliable, offering essential insights into educational service quality from parents' perspectives.